Interrogating LeftTube: ContraPoints and the Possibilities of Critical Media Praxis on YouTube. (September 2021) - Maddox, Jessica; Creech, Brian
For the past several years, media commentary and cultural analysis has grown increasingly fixated on YouTube as a radicalization hub, particularly around extremist, alt-right content. However, a growing community of leftist YouTube content creators, loosely coalescing into the platform's "LeftTube, " have developed dialogic relationships with some of YouTube's most extreme content. This work focuses on one specific LeftTube creator, ContraPoints, to explore how those on the political left engage with YouTube's cultural and technical affordances to challenge alt-right ideology. Through a textual analysis of ContraPoints' top thirty videos, we identified three main discursive strategies: practicing deradicalization strategies on YouTube; establishing alt-right individuals as an intentional audience; and developing a language for escaping alt-right logics. ContraPoints, and her rightful critics, demonstrate how political subjectivities are created and contested within YouTube as both a technical and cultural space.